EFFECT OF SPROUTING TIME ON PROXIMATE COMPOSITION AND ASCORBIC ACID LEVEL OF MUNG BEAN (VIGNA RADIATE L.) AND CHICKPEA (CICER ARIETINUM L.) SEEDS - T. Masood; H. U. Shah; A. Zeb (Journal of Animal and Plant Sciences, 2014)
This study was conducted to investigate the effect of different sprouting times on proximate composition, total energy and ascorbic acid content of mung bean (Vigna radiate L.) and chickpea (Cicer arietinum L.) seeds. Seeds were sprouted for 24, 48, 72, 96 and 120 h under dark at 25 °C ±2. Moisture contents, crude protein, ash and crude fiber contents were significantly increased from 9.75 %, 20.65 %, 2.75 % and 5.65 % to 62.67 %, 26.80 %, 3.67 % and 8.96 % respectively after 120 h of sprouting. While crude fat, carbohydrate and total energy content significantly decreased from 3.79 %, 57.41 % and 346.3 kcal 100 g-1 to 2.97 %, 47.75 % and 325.3 kcal 100 g-1 respectively after 120 h of sprouting. Higher percent improvement over control in moisture, ash and crude protein was recorded in chickpea than mung bean seeds. In contrast more % losses over control in crude fat, carbohydrates and total energy were found in mung bean than chickpea seeds after 120 h sprouting. Ascorbic acid contents in mung bean and chickpea increased significantly from zero to 20.78 mg 100 g-1 and 9.94 mg 100 g-1 respectively after 120 h of sprouting. Improvement in ascorbic acid over control samples was greater in mung bean (3700 %) than chickpea sprouts (994 %). It can be concluded from the study that sprouting for 120 h brought maximum improvement in the nutritional quality of mung bean and chickpea.
Keywords: mung bean; chickpea; sprouting time; proximate composition; ascorbic acid